Análise espacial e temporal da eficiência relativa em universidades federais brasileiras sob a política pública REUNI - Moreira, Ney Paulo (2018)
The purpose of this study was to carry out an analysis of the efficiency of Brazilian Federal Universities inscribed in the REUNI, identifying their determining factors, as well as discussing aspects related to the spatial performance and dependence structure. A systematic literature review was written aiming to identify how the relative efficiency of Higher Education Institutions has been approached. The Data Envelopment Analysis was carried out to measure the efficiency score of 52 universities from 2008 to 2015. The Tobit model was used to determine factors associated with performance. The geostatistics was also used to identify the structure of efficiency special dependence among institutions by means of semivariograms analysis. Results show a review of the current state of efficiency of Higher Education Institutions, focusing on the discussion of terms and concepts to analyze the efficiency of such institutions. The applied research consisted of empirical studies for the same purpose in different institutions. The applied research was found to use three different approaches for the analysis of relative efficiency, as follows: (i) performance indicators, (ii) parametric methods, and (iii) non-parametric approaches. Brazilian Federal Universities operated below their potential in the period under study, showing a decrease in performance over time, especially in 2009, with gradual recovery in the following years. By analyzing the student-professor ratio and the service provided by the professors to master and PhD students, universities appeared to become more uniform over time. Regarding factors related to efficiency, greater ratios student-professor and student-servant showed a positive relationship with the performance, as well as the association between the sizes of the institutions with the higher efficiency score. The quantity of campuses found out of headquarters showed a negative relationship with the efficiency of universities, and a spatial dependence for the efficiency was found in the period under study, leading to a decrease of dependence over time. The spatial distribution of the performance of universities showed great length of the low efficiency in 2009 with enlargement of areas, which indicate intermediate level of efficiency in the following years, and concentration of higher efficiency universities in areas clustered within all regions of the country.